Freedom of printing in the Courts and in the Constitution of Cádiz of 1812 - Fernández Rodríguez, José Julio (2008)
The freedom of the press was one of the most important matters incorporated in the Constitution of Cadiz of 1812, representing a breaking between the old preservative regime and the assumption of the values of liberalism that allows the intervention of the society in the public sphere without previous control of the organs of power, trying with this inicial step the change of the political system. The opposition of those two conservative parties supposed the starting point for the «natural law» defense of a series of fundamental rights and public liberties of the human being only for the fact of being a human being. In all this process towards the consolidation of liberalism as an alternative of a new political system, the written press played a extremely important role since it allowed the diffusion of the new ideas and information in favor of the society; there is the great importance that the freedom of the press had to obtain this consolidation.